Effects of Dry crops Rotation on field for soil fertilities changing and rice yield on raining season in Xienghone District, Sayaboury Province - PHOMMACHANH, Ladthakone; THONGMANY, Khammeung; Salitxay, Timnoy; LOCHAMYEU, Chanthvong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The problem of low soil fertility is the main reason for the decrease in rice yield due to the properties of the soil with low amount of nutrients in the soil, low density of the soil, acidity and alkalinity and minerals in the soil as well as the amount of organic matter which is the main determinant for rice yield and good quality. Crop rotation during the dry season in rice fields is more effective than single rice cultivation which can improve the quality of the soil and directly affect the yield of rice in the next season (year-old rice). The purpose of this research is to study the effect of changing the soil properties and the annual rice yield from planting dry season crops instead of planting dry season rice. It was implemented in rice paddy area of farmers in Xienghone district, Sayaboury province. There is a RCBD (Randomized Complete Block Design) experimental plan with 4 experiments and 3 replications: 1) Rice planting only (control factor) 2) Watermelon planting 3) Green soybeans planting and 4) Chilies planting. The data collection will be obtained from each sampling area of 5 points, then the data will be averaged, then the data will be analyzed with the Sirichai Statistic 6.07 program to find the deviation at the 95% confidence level. The results of the experiment show that the system of Green soybeans planting has a better yield of 4,646.23 kg/hectare. However, crops rotation during the dry season in rice fields is very necessary, especially for crops that use less water than rice cropping, to restore and improve the fertility of the soil, as well as to drop the cycle of insect pests of rice that may cause damage to rice production during the rainy season.